A focal extramedullary hematopoiesis of the spleen in a patient with essential thrombocythemia presenting with a complicated postoperative course: a case report - Kiyotaka Hosoda; Akira Shimizu; Koji Kubota; Tsuyoshi Notake; Shinsuke Sugenoya; Koya Yasukawa; Hikaru Hayashi; Ryoichiro Kobayashi; Yuji Soejima (Surgical Case Reports, 2021)
Abstract Background Extramedullary hematopoiesis is a compensatory response occurring secondary to inadequate bone marrow function and is occasionally observed in essential thrombocythemia (ET). This disease usually presents as multifocal masses in the paravertebral or intra-abdominal region; however, formation of a focal mass in the liver or spleen is rare. In addition, ET is characterized by increased platelet count and shows a tendency toward thrombosis and, occasionally, bleeding. Serious bleeding is common in ET patients, caused by the decrease in or abnormalities of von Willebrand factor (vWF) as a consequence of the precipitous rise in platelets. Therefore, strict management of platelet count using medication is crucial in patients with ET who require invasive procedures, especially splenectomy. Case presentation A 68-year-old man with ET was found to have an enlargement of a focal splenic tumor. Imaging findings revealed that the tumor was likely a hemangioma or hamartoma; however, the possibility of malignant disease could not be completely ruled out because of short-term tumor enlargement, and we conducted a splenectomy. The surgery was uneventful, but the patient presented with severe polycythemia and vWF abnormalities postoperatively, which resulted in bleeding from the drain insertion site and wound, epistaxis, and hemorrhoidal bleeding. Three months after discharge, polycythemia still persisted and the level of vWF gradually decreased. With a decrease in vWF, the patient suffered from an increased bleeding tendency. Therefore, the patient has been referred for bone marrow transplantation and is currently awaiting a suitable donor. Conclusions Extramedullary hematopoiesis should be listed as a differential diagnosis of focal enlarged splenic tumors, especially in patients with myeloproliferative disorders. Additionally, in splenectomy for ET patients, careful perioperative management taking into consideration the conflicting features of a tendency toward thrombus formation and bleeding is necessary.